Development of digital modules for English subjects for fourth grade elementary school students - Pratiwi, Syahnaz Nabila Anjani; Nurhikmah, Nurhikmah; Anwar, Citra Rosalyn (Univeritas Papua, 2024)
The study aims to develop a digital module for English subjects in elementary schools. The development follows the flow of the ADDIE model. The study subjects were 2 validators and 9 students during the small group trial and 31 during the large group trial. Data collection used a needs identification questionnaire, a validation questionnaire for material experts and design experts, a small group trial questionnaire, and a test. Data were calculated by calculating scores and percentages for validity and student responses, while the effectiveness test used the Wilcoxn and n-gain tests. The study results found that identifying student needs was in the required qualifications. The results of the validity level of the digital module from the assessment of the material expert validator were 89% and the media/design expert 94% (very valid). The results at the level of practicality obtained from the analysis of the small group response questionnaire were 97 (very practical). Furthermore, the level of effectiveness of the digital module was 0.8 (high), with significant test results showing a significant difference before and after learning. It was concluded that the product can be used in the classroom learning process to teach students English.